Analysis of the Effect of Profitability and Solvency Ratios on Share Prices at PT Summarecon Agung Tbk - Fahrozi Wirakusuma; M. Rimawan; Aris Munandar (JEKAMI Journal of Accounting, 2024)
This research aims to determine the effect of Net Profit Margin, Debt to Equity Ratio on share prices at PT Summarecon Agung Tbk. based on whether PT Summarecon Agung Tbk's financial reports are running well or not. This sample was taken directly from the financial reports on the official website www.summarecon.com. The analytical method used is a quantitative analysis method, the data used is secondary data with data collection techniques in the form of document analysis and literature study. The data analysis technique used is purposive sampling. It can be concluded that the share price at PT Summarecon Agung Tbk experienced fluctuations in 2012 - 2022 which, it can be seen that net profit after tax in 2015 and 2016 decreased, this was caused by losses from two subsidiaries as well as the weakening of the rupiah against the dollar which caused the burden of paying the company's debt. increase. Sales decreased in 2016 - 2020. This was due to raw material commodity prices and an increase in cost of goods sold. Total Debt has increased from 2012 - 2020. Meanwhile, Total Equity has decreased in 2020. Share prices tend to fluctuate at the average share price shown in the last 11 years and this is a factor that hinders the stability of Pt Summarecon Agung Tbk because it is influenced by the level of demand and supply of share prices by investors.